A response surface methodology for the use of MIL‐101 as a catalyst for the one‐step synthesis of lactide - Clara Novia; Catia Angli Curie; Misri Gozan (Indonesian Journal of Biotechnology, 2023)
Lactide is a vital monomer for producing high molecular weight polylactic acid (PLA) through ring‐opening polymerization. This study synthesized crude lactide from L‐lactic acid with MIL‐101 as the catalyst. MIL‐101 is a metal‐based catalyst with organic ligands (MOF) that was prepared by reacting Cr(NO3)3.9H2O with terephthalic acid (BDC). The formation of MIL‐101 was confirmed from Fourier‐transform infrared (FTIR) analysis. The role of MIL‐101 and the effect of temperature, time, and MIL‐101 loading, as well as their interactions in the conversion of lactic acid to crude lactide, were then investigated using the response surface method (RSM). Crude lactide was analyzed using 1H‐nuclear magnetic resonance (NMR) spectroscopy to confirm the presence of lactide. The RSM results indicated that the highest conversion of 22.84% can be obtained using a temperature of 175 °C, 1.5% w/w MIL‐101 loading, and a reaction time of 5 h. The RSM model showed that the interaction of MIL‐101 loading and reaction time strongly affected the conversion of lactic acid to lactide, with a P‐value of 0.0021 and an F‐value of 50.45. In contrast, the interaction of catalyst loading and temperature did not significantly affect the conversion of lactic acid to lactide, with a P‐value of 0.2565 and an F‐value of 1.75.